2020
DOI: 10.1111/1750-3841.15363
|View full text |Cite
|
Sign up to set email alerts
|

Changes in free amino acids of fermented minced peppers during natural and inoculated fermentation process based on HPLC‐MS/MS

Abstract: Free amino acids (FAAs) participate in the synthesis of quality characteristic ingredients and taste substances in fermented minced peppers (FMPs), and they can be affected by fermentation method and time. In this study, changes in FAAs of FMP during natural fermentation (NF) and inoculated fermentation (IF) process were characterized by HPLC‐MS/MS. The results showed that a total of 20 FAAs were identified, including 8 essential amino acids (AAs), 2 semiessential AAs, and 10 nonessential AAs. Comparing with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Fermentation is the main stage for the formation of other amino acids; the concentration of serine and threonine positively correlated with the fermentation stage, reaching 0.35 ± 0.02g/100g and 1.57 ± 0.03g/100g dry weight on day 17 of fermentation, respectively. Proteases produced by microorganisms that hydrolyze proteins into amino acids also contribute to the increase in amino acid content ( Wang et al, 2020 ). Furthermore, after 1.5 years of aging, the serine concentration reached 0.58 ± 0.02g/100g dry weight and then declined continuously.…”
Section: Resultsmentioning
confidence: 99%
“…Fermentation is the main stage for the formation of other amino acids; the concentration of serine and threonine positively correlated with the fermentation stage, reaching 0.35 ± 0.02g/100g and 1.57 ± 0.03g/100g dry weight on day 17 of fermentation, respectively. Proteases produced by microorganisms that hydrolyze proteins into amino acids also contribute to the increase in amino acid content ( Wang et al, 2020 ). Furthermore, after 1.5 years of aging, the serine concentration reached 0.58 ± 0.02g/100g dry weight and then declined continuously.…”
Section: Resultsmentioning
confidence: 99%
“…20,000 mg/L ( 23 ). During the fermentation process of peppers, the arginine content was higher in peppers inoculated with lactic acid bacteria than that of the control group without inoculation of lactic acid bacteria ( 24 ). Also, other studies ( 25 , 26 ) also show that during L. plantarum fermentation, the amino acid content of the fermentation system was significantly increased ( p < 0.05), which is consistent with the results of this study.…”
Section: Resultsmentioning
confidence: 99%
“…This could be attributed to the fact that the enzymatic activities of PPYAT are activated by oxygen under aerobic conditions, and vice versa. Previous study have demonstrated that the activity of PPYAT could be influenced by different substances; for example, its activity on S. cerevisiae was higher in cassava beer than The top-class of the KEGG enrichment pathway and pharmacological action of nine main compounds produced by Lactiplantibacillus plantarum during fermentation of Polygonati Rhizoma; *information on the pharmacological action is obtained from the literature (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38).…”
Section: Regulation Of Amino Acid Biosynthesismentioning
confidence: 99%
“…In addition, the fermentation process also produces free amino acids, active peptides, polysaccharides, and other substances. Wang et al employed the HPLC-MS method to prove that the components of fermented chili powder (FMPs) were transformed during fermentation, and FMPs had the higher quantity of free amino acids ( 28 ). The results of Liu et al indicated that fermentation enhanced the anti-obesity effect of pepper on the HFD mice ( 29 ).…”
Section: Discussionmentioning
confidence: 99%